“Evaluación de tres dosis de micorrizas en el cultivo de pimiento (capsicum annuum) en el cantón la Maná”. - Cabrera Ripalda, Geomayra Lilibeth (2021)
The present investigation was carried out in the Chipe Hamburgo N ° 2 sector, belonging to the El Triunfo parish of La Maná canton. The proposed objectives were: Analyze some variables of growth and production of the pepper crop, determine the appropriate dosage of mycorrhiza in the pepper crop, economically analyze the treatments in the production of the pepper crop with the application of three doses of mycorrhizae. The completely randomized design (DCA) was used, with four treatments and five repetitions, the treatments under study were: T1: 10g, T2: 20g, T3: 30g and T4: absolute control. The variables evaluated were: days to flowering, plant height at 15.30 and 45 days, number of fruits per treatment, length and diameter of fruits, weight of fruits, yield per hectare, and economic analysis. The following results were obtained: less days to flowering in the dose of 20g with 19.60 days from the transplant, greater plant height in the dose 20g with 12.63, 41.98 and 75.55 cm in the evaluated ages. For the number of fruits the best results were obtained with the dose of 20 g with 34.20 fruits per treatment; Regarding the length and diameter of the fruit, the dose of 20g achieved the best results with 16.71 and 8.27 cm respectively; the highest fruit weight registered the dose of 20 g with 722.91 grams on average. The highest yield per hectare was given with a dose of 20 g, obtaining 25,750 k / ha. Regarding the highest income per hectare, I present with the application of 20 g with USD. 41200, while the best benefit / cost ratio was obtained with the 20 g dose with a return of USD. 1.79 for each monetary unit of production.